Microglial Polarization in the Pathogenesis and Therapeutics of Neurodegenerative Diseases - Isidre Ferrer (Frontiers Research Topics, 2018)
Microglia-mediated neuroinflammation is one of the shared prominent hallmarks among various forms of neurodegeneration. Depending on the milieu in which microglia become activated, the polarization of microglia shows to be heterogeneous with diverse functional phenotypes that range from pro-inflammatory phenotypes to immunosuppressive phenotypes. Therefore, targeting microglial polarization holds great promise for the treatment of neurodegeneration. This eBook focuses on the potential mechanisms of microglial polarization that are critically associated with a broad spectrum of neurodegenerative diseases, including Parkinson's disease (PD), Alzheimer's disease (AD), Amyotrophic lateral sclerosis (ALS), Huntington's disease (HD), Traumatic brain injury (TBI), glaucomatous neurodegeneration and prion diseases. This topic also involves the therapeutic targeting of microglial polarization by nutritional and pharmacological modulators. Moreover, this topic describes advanced technologies employed for studying microglia. Age-related changes in microglia functions are also discussed. Overall, this eBook provides comprehensive understandings of microglial polarization in the course of neurodegeneration, linking with aging-related microglial alterations and technologies developed for microglial studies. Hopefully, it will also give comprehensive insights into various aspects of therapeutic treatment for neurodegeneration, through targeting microglial polarization.